A síndrome de Burnout entre profissionais de enfermagem: um estudo observacional em um hospital da rede SUS - Caixeta Neto, Américo José (2018)
The development of studies that involve the occupational context of nursing has been extremely relevant, since these professionals are crucial participants in health actions. In this regard, the present study investigated the prevalence of Burnout Syndrome and the risk and protective factors associated with the occupational context of nursing staff in an Emergency Room of a SUS hospital in Uberlândia/MG. The main objectives were: a) to analyze the prevalence of Burnout Syndrome among nursing professionals; b) to characterize the sociodemographic and labor profile of nursing professionals; c) to compare the levels among the professionals approached according to sociodemographic and labor variables d) to investigate the possible risk factors for the manifestation of the syndrome. To achieve the aim of this study, an observational sectional study with a quantitative approach was chosen. The study was developed in the Emergency Room of the Hospital de Clínicas of the Federal University of Uberlândia (HCU/UFU), where two self-applicable instruments were used for data collection: a questionnaire with sociodemographic and labor information and the questionnaire for Burnout Syndrome evaluation, the Maslach Burnout Inventory-Human Service Survey (MBI-HSS). The data were analyzed by the Statistical Package for the Social Sciences 22.0 program. 111 professionals were investigated. The results showed a predominance of females (70.3%). Professionals with high school education were the most representative (83.8%), and the most predominant age group was 40 to 49 years old. It was found that 11.7% of the professionals were affected by Burnout Syndrome, most of them male (53.8%), statistically significant (p=0.04). The highest incidence was observed in unmarried individuals (46.2%), and the most affected age group was between 30 and 39 years old (33.3%). Professionals with high school education (nursing auxiliaries and technicians) manifested the disease in highest percentage, 76.9%. Regarding the type of employment, the public employees (69.2%) were the most representative. Newly active professionals were the most affected by the disease. Sociodemographic and labor data did not present a significant correlation with the syndrome. The leisure time variable did not contribute as a protective factor and the practice of physical exercises was shown to be a positive factor, contributing to minimize the manifestation of the syndrome, but it was not of statistical significance (p=0.23). In order to deepen the research on Burnout Syndrome and its manifestations in the occupational context of nursing staff, more studies to approach bigger populations and to identify other factors that may be associated with the manifestation of the syndrome and also to reflect over which measures can be adopted in the sense of modifying such factors are needed.